Modifcation of thin metal and ceramic filmsby UV and IR laser adiation; Proceedings of SPIE; Vol. 5483 - Orlovskii V. M.; Tarasenko V. F. Victor Fedotovich; Fedenev A. V.; Alekseev S. B.; Goncharenko I. M.; Koval N. N. Nikolay Nikolaevich; Lipatov E. I.; Trtica M. A.; Gaković B. M.; Petkovska L. T. (2004, 2004)
Title screen